2020
DOI: 10.1039/c9ta12904a
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of surface defects to achieve hysteresis-free inverted perovskite solar cells via quantum dot passivation

Abstract: We fabricated the defect passivation of perovskite solar cells using CdSe/ZnS quantum dots. The efficient defect passivation of reduces the trap charge density and elongates the charge carrier life time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…In contrast to early research on the structure of conventional PSCs, the inverted planar structures (n-i-p or p-i-n) have been investigated owing to their ease of manufacturing, low-temperature and low-cost processing, and compatibility with flexible beds in PSC [2][3][4]. According to several studies, inverted planar devices have shown efficiency of above 20% for producing conventional structures, which is very promising [5,6]. To the best of our knowledge, despite recent advances in PSCs, inverted planar PSCs have garnered less attention and only a few studies have been conducted in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to early research on the structure of conventional PSCs, the inverted planar structures (n-i-p or p-i-n) have been investigated owing to their ease of manufacturing, low-temperature and low-cost processing, and compatibility with flexible beds in PSC [2][3][4]. According to several studies, inverted planar devices have shown efficiency of above 20% for producing conventional structures, which is very promising [5,6]. To the best of our knowledge, despite recent advances in PSCs, inverted planar PSCs have garnered less attention and only a few studies have been conducted in this field.…”
Section: Introductionmentioning
confidence: 99%
“…102 Hanmandlu et al incorporated CdSe/ZnS QDs into the MAPbI 3 perovskite to passivate the surface charge traps and grain boundaries. 104 Based on this passivation strategy, the target devices exhibited PCE close to 20% with suppressed hysteresis in the J-V characteristics and fill factor of 81.44%. Moreover, they achieved long-term stability under an N 2 atmosphere at 50 , retaining 80 and 75% of their initial PCE after 720 h and after ℃ 2400 h, respectively; in contrast, the control device lost 70% after 360 h.…”
Section: Pbs Qds Hybrid With All-inorganic Perovskite Filmsmentioning
confidence: 96%
“…Several methods, including modifying the composition [ 68 ] and interface of PPVs with chemicals or NPs, [ 69,70 ] have been proposed for enhancing the efficiencies of PPVs. However, the use of plasmonic NPs to boost the efficiencies of PPVs for indoor applications is rarely mentioned.…”
Section: Indoor Perovskite Photovoltaicsmentioning
confidence: 99%